Feasibility Study on the Use of Multiple-Reference Frames for Computations of Propeller-Hull Interaction in OpenFOAM® - Mühlhölzer, Rosa (My University, 2012)
By analyzing the optimum trim of ships in different operating conditions with Reynolds- Averaged Navier-Stokes equation computations (RANSE) the fuel consumption efficiency can be increased. Because the influence of the trim on the propulsive efficiency is usually approximated the propeller-hull interaction shall be included in the computation to improve the analysis of the optimum trim. Therefore, a setup for future computation of propeller-hull interaction has been carried out using the open source software Open- FOAM and different methods to compute rotational motion which are available in Computational Fluid Dynamics (CFD). A feasibility study on the different methods was done by computing the open water characteristics of the propeller and validating the setup with given model tests. Steady methods like the Single Reference Frame method (SRF) and the Multiple Reference Frame method (MRF) have been used to analyze the performance of a propeller in an open water test. For pre-processing the mesh generator of OpenFOAM snappyHexMesh has been used and an automation process to generate the mesh has been developed. Different methods of generating the rotational and non-rotational zones, which are needed for the MRF method, have been investigated. With the introduced automation process it is possible to compute the performance of a propeller in the open water test by just using open source software. The use of the SRF and MRF method combined with the used grid generation method can be seen as a feasible approach for computing open water characteristics, but when it comes to propeller-hull interaction further investigations are required.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport